2016
DOI: 10.1007/s10899-016-9623-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking, Delay Discounting, and Time Perspective in Adolescent Gamblers: An Experimental Study

Abstract: Previous research has demonstrated that adult pathological gamblers (compared to controls) show riskproneness, foreshortened time horizon, and preference for immediate rewards. No study has ever examined the interplay of these factors in adolescent gambling. A total of 104 adolescents took part in the research. Two equal-number groups of adolescent non-problem and problem gamblers, defined using the South Oaks Gambling Screen-Revised for Adolescents (SOGS-RA), were administered the Balloon Analogue Risk Task (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 78 publications
6
23
2
Order By: Relevance
“…More specifically, at-risk and problem gamblers appear to be more prone to focus on the immediate outcomes of their behavior than both non-gamblers and non-problem gamblers. This finding extends evidence obtained on both adult and adolescent samples (Hodgins and Engel, 2002; Whiteside et al, 2005; Toplak et al, 2007; Daugherty and Brase, 2010; MacLaren et al, 2012; Cosenza et al, 2014, 2016; MacKillop et al, 2014; Cosenza and Nigro, 2015; Ciccarelli et al, 2016a). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…More specifically, at-risk and problem gamblers appear to be more prone to focus on the immediate outcomes of their behavior than both non-gamblers and non-problem gamblers. This finding extends evidence obtained on both adult and adolescent samples (Hodgins and Engel, 2002; Whiteside et al, 2005; Toplak et al, 2007; Daugherty and Brase, 2010; MacLaren et al, 2012; Cosenza et al, 2014, 2016; MacKillop et al, 2014; Cosenza and Nigro, 2015; Ciccarelli et al, 2016a). …”
Section: Discussionsupporting
confidence: 85%
“…As regards to delay discounting, the results are in accordance with previous research demonstrating that pathological gamblers devalue or discount delayed rewards to a greater extent than non-gamblers and non-problem gamblers do (Petry and Casarella, 1999; e.g., Alessi and Petry, 2003; Madden et al, 2011; Michalczuk et al, 2011; Brevers et al, 2012; Miedl et al, 2012; Petry, 2012; Kräplin et al, 2014; see also Gray and MacKillop, 2014; Cosenza and Nigro, 2015; for a review see Wiehler and Peters, 2015; Cosenza et al, 2016; Nigro and Cosenza, 2016; Ciccarelli et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found no difference in the amount of risky choices between gamblers and controls. This result is contrary to most studies on PG, which report increased risky taking in PG patients (6,17,76). One could argue, that the methodical changes in our task design also play a role in the missing risk taking effect, because it reduces the motivation to engage in risky behavior.…”
Section: Additional Remarks On Our Findings On Decision Making In Pgcontrasting
confidence: 85%
“…The seemingly inconsistent association of future time perspective with condom use could be due to the contingencies surrounding condom-less sexual intercourse for sex workers, that is with casual partners condom use were overall lower but financial incentives could be driving this behavior more than time perspective (Sosa-Rubí et al, 2018). Other research has shown that future time perspective is related to monetary delay-discounting (Cosenza, Griffiths, Nigro, & Ciccarelli, 2017;Gollner, Ballhausen, Kliegel, & Forstmeier, 2017); however, monetary delay-discounting has also been shown to be a distinct type of decision-making when compared to sexual discounting (Jarmolowicz, Bickel, & Gatchalian, 2013;Johnson & Bruner, 2012). Taken together, further research is needed into the role future time perspective might have on these sexual decision-making processes because time perspective is malleable and thus could inform future intervention development if it is a relevant variable (Stein, Tegge, Turner, & Bickel, 2018;Stein et al, 2016).…”
Section: Domains Delay Length Reward Magnitude and Individual Diffmentioning
confidence: 98%